Uveitis after COVID-19 Vaccination - Je Hyung Hwang (Case Reports in Ophthalmology, 2022)
This report describes a case of acute uveitis following COVID-19 vaccination. A 21-year-old patient was referred to our department for decreased visual acuity and injection of the left eye. Two days prior, the patient received her second dose of the severe acute respiratory syndrome coronavirus 2 vaccine (BNT162b2, Pfizer-BioNTech). On ocular examination, her left eye’s best-corrected visual acuity was 20/250, and its intraocular pressure was 16 mm Hg on a noncontact tonometer. Hypopyon, 4+ cells, and flares were observed in the anterior chamber. The patient was diagnosed with acute uveitis. She received topical dexamethasone (0.1%) hourly and systemic prednisone (50 mg/day). After 7 days, her inflammatory symptoms were mostly resolved. COVID-19 vaccination can cause acute anterior uveitis, which is responsive to steroids.